1985
DOI: 10.1111/j.2044-8341.1985.tb02647.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital herpes: The psychological consequences

Abstract: This study investigated the psychological consequences of genital herpes among 42 men and women. The impact of the disease was assessed relative to five life-areas: sexual functioning, interpersonal relationships, emotional responses, self-concept, and work or school performance. The impact of genital herpes can be best understood when placed in the context of the ethical issues raised by the disease, the individual sufferer's personal development, psychodynamics and self-concept, and the meaning which genital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 3 publications
5
71
1
Order By: Relevance
“…[25][26][27] However, Brookes et al,3 seeking to overcome the difficulties of such uncontrolled cross sectional designs, obtained self ratings on a variety of variables relative to before infection in long term herpes sufferers. The study had the problems of other retrospective data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] However, Brookes et al,3 seeking to overcome the difficulties of such uncontrolled cross sectional designs, obtained self ratings on a variety of variables relative to before infection in long term herpes sufferers. The study had the problems of other retrospective data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Some sufferers have reported that herpes only became a major issue in their lives when the media discovered the disease (7). Indeed, there appears to be less stigma attached to genital herpes and sexually transmitted diseases (STDs) in general in some of the other European countries (notably Denmark and the Netherlands), where attitudes toward sexual activity and STDs are less condemnatory than in the United Kingdom and the United States.…”
Section: )( 1)mentioning
confidence: 95%
“…The authors concluded that only 33% had adapted to the disease in a satisfactory manner. The psychologic consequences of genital herpes were examined in 42 individuals with herpes who were seeking counseling or psychotherapy (Drob, Loemer, & Lifshutz, 1985). Findings revealed that the majority felt less sexually desirable, depressed, and worried about recurrences, and were pessimistic about the future course of the disease.…”
Section: Psychosocial Consequences Of Genital Herpesmentioning
confidence: 99%